Quality of Service, Satisfaction and The Effect Towards Customer Loyalty - Suwarsito; Syukri Ghozali; Herlin Widasiwi Setianingrum; Sufi Alawiyah (Jurnal Manajemen Bisnis, 2020)
The purpose of the research is to analyze and identify the effect of the service quality and satisfaction variables toward customer loyalty. the data collection method used in this researchi uses the survey method with questionnaires. This research population is the customers of Indosat Unlimited in Depok. From the results of the analysis, it shows that the service quality significantly influences the customer loyalty, proven by the t significant value of 0.000 smaller that α 0.05 with the coefficient of 2.537. Quality of service has a significant effect on the customer loyalty ishown by the t significant value 0.000 less than 0.05. service quality and satisfaction significantly influence the customer loyalty shown by F value of 0.000 smaller than 0.05 and are able contribute to the customer loyalty variables of 0.504 or 51.7%. the remaining 48.3% is influenced by other variables that are not analized in this research.